Evaluation of crumb rubber modification and short-term aging on the rutting performance of bioasphalt. (30th December 2018) - Chen, Yu; Ji, Chuanjun; Wang, Hainian; Su, Yumin
Highlights: The bioasphalt exhibited higher rutting resistance than the virgin binder after short-term aging. Higher rutting resistance of bioasphalt was observed with the addition of crumb rubber particles. Crumb rubber had an upper limit role on the elastic behavior of binders with the increase of loading frequency. Rutting factor G * /sin(d) tests was still a valuable tool for the rutting resistance ranking of modified binders. Abstract: In this study, the high temperature performances of ten combinations of bioasphalt and crumb rubber particles were evaluated by DSR and MSCR tests. Testing results indicated that short-term aging and crumb rubber modification increased the complex shear modulus and reduced the phase angle. In addition, the crumb rubber modified bioasphalt significantly reduced the unrecovered creep compliance and increased the percentage recovery. It can be concluded that the bioasphalt exhibited higher rutting resistance than the virgin binder and it can be used like traditional binder in term of rutting performance. In addition, crumb rubber greatly increased the rutting performance of bioasphalt.